Investigation of the earthquake-induced liquefaction and seismic amplifications after Pazarcık (Mw 7.7) and Elbistan (Mw 7.6) earthquakes - Yildiz, Ozgur; Zeybek, Abdulhakim; Sonmezer, Yetis Bulent (Springer, 2024)
The earthquakes in Pazarc & imath;k (Mw 7.7) and Elbistan (Mw 7.6), occurring along the East Anatolian Fault Zone (EAFZ) on February 6, 2023, caused significant damage and destruction to the built environment within the affected area. In this study, the preliminary site investigations were conducted in the G & ouml;lba & scedil;& imath; district, where the impacts of both earthquakes were severely felt, offering scientifically valuable information regarding the soil damage. Comprehensive liquefaction analyses were performed using the geotechnical laboratory test data on soil specimens collected from the G & ouml;lba & scedil;& imath; district. These analyses confirmed the liquefaction-induced ground failures observed immediately after the two earthquakes. Furthermore, microzonation data collected in the G & ouml;lba & scedil;& imath; district were consolidated, and seismic site response analyses were conducted. Simulations showed that local soils in the region could amplify seismic waves by a factor of two. Utilizing the calculated Peak Ground Acceleration (PGA) and amplification factors, GIS-based distribution maps of the entire area were developed. These maps serve as practical resources for practitioners and local planners, aiding in spatial settlement decisions and urban transformation planning. They contribute significantly to enhancing the understanding of earthquake hazards in the region.
Keywords: G & ouml;lba & scedil;& imath; Earthquake-induced damages; Seismic site amplification; Liquefaction